The E3 ubiquitin ligase MARCH3 controls the endothelial barrier. Issue 20 (26th September 2016) - Leclair, Héloïse M.; André‐Grégoire, Gwennan; Treps, Lucas; Azzi, Sandy; Bidère, Nicolas; Gavard, Julie
Abstract : Cell–cell contacts coordinate the endothelial barrier function in response to external cues. To identify new mediators involved in cytokine‐promoted endothelial permeability, we screened a siRNA library targeting E3 ubiquitin ligases. Here, we report that silencing of the late endosome/lysosomal membrane‐associated RING‐CH‐3 (MARCH3) enzyme protects the endothelial barrier. Furthermore, transcriptome analysis unmasked the upregulation of the tight junction‐encoding gene occludin ( OCLN ) in MARCH3‐depleted cells. Indeed, MARCH3 silencing results in the strengthening of cell‐cell contacts, as evidenced by the accumulation of junctional proteins. From a molecular standpoint, the FoxO1 forkhead transcription repressor was inactivated in the absence of MARCH3. This provides a possible molecular link between MARCH3 and the signaling pathway involved in regulating the expression of junctional proteins and barrier integrity. Abstract :